1999
DOI: 10.1021/jp992105y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of B2Lin (n = 1−4)

Abstract: Structures and energies of the binary B2Li n (n = 1−4) clusters are predicted with the HF, MP2, and B3LYP methods using the 6-31G(d) basis set, including energy evaluations at G2MP2 and CBS-Q and the larger 6-311+G(2d) basis set for B3LYP. All systems except B2Li4 are also computed with the CASSCF method because of spin contamination for several of the open-shell systems. These were followed by energy evaluations with multiconfigurational perturbation theory. The global B2Li minimum has a C 2 v triangular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Density of state (DOS) and band structures are collected in Figures 8 and 9. When our results are compared with the well-studied clusters by Nguyen et al [23], Srinivas et al [34] and Ying Li et al [12], we can conclude that our calculations are correct and compatible. The calculated bond length of BLi is 2.141 Å at the QCISD (2.174 Å at the CCSD (T)).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Density of state (DOS) and band structures are collected in Figures 8 and 9. When our results are compared with the well-studied clusters by Nguyen et al [23], Srinivas et al [34] and Ying Li et al [12], we can conclude that our calculations are correct and compatible. The calculated bond length of BLi is 2.141 Å at the QCISD (2.174 Å at the CCSD (T)).…”
Section: Resultssupporting
confidence: 79%
“…The B-B bond vibrational stretching frequency is 1118 cm −1 for B 2 Li and 1014 cm −1 for B 2 at B3LYP. Total energy of B 2 Li is −56.56928 au at HF (−56.72242 au at MP2, −56.99109 au at B3LYP and −56.72824 au at CASSCF), as shown by Srinivas et al [ 34 ]. B 2 Li second isomer is made up of two boron atoms and one lithium atom with a triangular geometric structure, and the angles of this molecule are 69.56°, 69.73° and 40.71°.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Compounds of boranes and borides indeed have spanned a large area of chemistry due to their aesthetically appealing structures and unique bonding features and the formation of cages and clusters . Among the borides, lithium borides have been extensively studied and showed that the lithium atom preferably forms a bridge around the central B−B bond .…”
Section: Introductionmentioning
confidence: 99%